If you mean: -3*(-2b-3)+7b then it is an algebraic expression that can be simplified to 6b+9+7b = 13b+9
Chat with our AI personalities
2B Multiplied by 3 plus B = 7B. Here is how it's worked out. You start with 2B, multiply that by 3 and you get 6B. Now all you have to do is add the last B, therefore adding 1B to equal 7B.
It is an equation and the value of b is 3
Sometimes you can think of things instead of letters, for example...3a + 2a = ?If that was 3 apples plus 2 apples equals ... ? then you could do it, right?3 apples + 2 apples = 5 apples3a + 2a = 5aAnd the same with MINUS...10b - 7b = ?10 bananas - 7 bananas = 3 bananas10b - 7b = 3bOf course, you can't add bananas and apples, you have to count them separately, so...3a + 4b + 7a - 2b= 3 apples + 4 bananas + 7 apples - 2 banana= 10 apples + 2 bananas= 10a +2b(You can't add these two together)After that it gets more complicated...
The question is worded amibiguously. Do you mean 3(7b)-2, or 3(7b-2)? 3(7b) - 2: 2 = 21b 2/21 = b 3(7b -2): 21b - 6 = 0. 21b = 6 b = 6/21 = 2/7.
1.Arithmetic.2.developmental math.3.pre-algebra.4.brain teasers.5.algebra.6.geometry.7.trigonometry.8.probability.9.statistics.10.pre-calculus.11.calculus.12.differential equations.13.linear algebra.